Differentiated Learning in Islamic Religious Education and Character Education - Indrianto, Nino; Maulida, Lutfi Laili (Universitas Islam Sultan Agung, 2025)
The purpose of this study is to comprehensively describe how teachers design and implement differentiated learning, as well as to identify various factors that facilitate and hinder the process. This research employs a qualitative approach. There are four subjects in this study: the principal, the vice principal of curriculum, Islamic religious education teachers, and grade 8 students. Data collection techniques included observation, interviews, and documentation. Data analysis in this study involves data collection, data condensation, data display, and drawing conclusions/verification. Data validity was ensured through source and technique triangulation. The results of this study are: 1) The planning stage begins with analyzing learning outcomes, creating learning objectives and their flow, and lesson planning. 2) The implementation stage begins with a diagnostic assessment and curriculum analysis, followed by the application of content, process, and product differentiation based on those results. 3) Supporting factors include support from the principal and adequate infrastructure, while the inhibiting factor is the difficulty educators face in managing the classroom.